Anti-inflammatory and Antioxidant Activity of Peptides From Ethanol-Soluble Hydrolysates of Sturgeon (Acipenser schrenckii) Cartilage - Yuan, Li; Chu, Qian; Wu, Xiaoyun; Yang, Bei; Zhang, Wei; Jin, Wengang; Gao, Ruichang (Frontiers in Nutrition, 2021)
Research has shown that cartilage containing chondroitin sulphate and protein presents versatile bioactivities. Chondroitin sulphate in cartilage is beneficial to activate the immune system while the protein/peptide has not been fully understood. The current study investigated the antioxidant and anti-inflammatory properties of ethanol-soluble hydrolysates of sturgeon cartilage (ESCH) prepared through hot-pressure, enzymatic hydrolysis and ethanol extraction. UV spectrum, IR and agarose gel electrophoresis results suggested the successful exclusion of chondroitin sulphate from peptides. Nitric oxide (NO) floods in cells activated by inflammation. It was inhibited when administrated with ESCH. To further explain the observed anti-inflammatory activity, ESCH was separated with Sephadex G-15 into 3 components, among which F3 showed a higher NO inhibition rate and significantly reduced the production of the proinflammatory cytokine IL-6. In addition, the yield of IL-10 increased. Western blotting suggested that F3 downregulated the NO content and IL-6 level by suppressing Mitogen-activated protein kinases (MAPK) channels. Moreover, both ESCH and F3 showed DPPH and ABTS free radical scavenging abilities which possibly relate to the anti-inflammatory property. These results indicated that ESCH behaves anti-inflammatory and antioxidant activities. Cartilage may be a good source to produce anti-inflammatory peptides.